2011
DOI: 10.1128/jvi.00883-10
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Control of Viral Shedding following Rhesus Cytomegalovirus Challenge in Rhesus Macaques

Abstract: The use of animal models of human cytomegalovirus (HCMV) infection is critical to refine HCMV vaccine candidates. Previous reports have demonstrated that immunization of rhesus monkeys against rhesus cytomegalovirus (RhCMV) can reduce both local and systemic replication of RhCMV following experimental RhCMV challenge. These studies used prime/boost combinations of DNA expression plasmids alone or DNA priming and boosting with either inactivated virion particles or modified vaccinia virus Ankara (MVA) expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 47 publications
2
49
2
Order By: Relevance
“…In the RM model, it was previously demonstrated that vaccination with subunit vaccines consisting of pp65b (with or without IE1) as T cell-inducing components and gB as neutralizing antibody-inducing component reduced RhCMV viremia and shedding (44)(45)(46). However, our data also suggest that T cell responses to antigens other than pp65 play an important role in the protective effect of RhCMV infection against ΔUS2-11 challenge.…”
Section: Vaccine-induced Pp65-specific T Cells Do Not Recapitulate Thcontrasting
confidence: 53%
See 3 more Smart Citations
“…In the RM model, it was previously demonstrated that vaccination with subunit vaccines consisting of pp65b (with or without IE1) as T cell-inducing components and gB as neutralizing antibody-inducing component reduced RhCMV viremia and shedding (44)(45)(46). However, our data also suggest that T cell responses to antigens other than pp65 play an important role in the protective effect of RhCMV infection against ΔUS2-11 challenge.…”
Section: Vaccine-induced Pp65-specific T Cells Do Not Recapitulate Thcontrasting
confidence: 53%
“…In this previous work, it was shown that this vaccination regimen, while unable to protect against superinfection with RhCMV, reduced local and systemic viremia as well as viral shedding. Moreover, reduction in shedding correlated with the magnitude of pp65-specific T cell responses (44). In our hands, the heterologous prime-boost vaccination induced a robust CD4 + and CD8 + T cell response to pp65b that in the blood was similar in magnitude to pp65-specific T cell responses elicited by RhCMV infection.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Another phase II study, using solid organ transplant recipients, showed 50% efficacy in controlling viremia in high-risk patients (35). In addition, vaccination studies with gB in rhesus macaques and subsequent rhesus CMV (RhCMV) challenge showed significantly reduced RhCMV DNA in plasma (36,37). Finally, a number of studies using the guinea pig model demonstrated that congenital infection and mortality in pups were reduced following gB DNA or recombinant protein subunit vaccination strategies (38).…”
mentioning
confidence: 99%